2023
DOI: 10.5772/intechopen.109928
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Technologies and Guidelines Set for Water Reuse

Abstract: Water reuse is considered a practice that is currently embraced worldwide owing to the exacerbated water crisis, which is the result of several factors such as the increasing world population, urbanization, industrial sector, global climate change, limited water resources, and agricultural activities. Water reuse is not used intensively only in arid and semi-arid regions, which are characterized by limited water supply but can also be applied in countries that possess sufficient water resources (e.g., Brazil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Desalination technologies include several processes that may be classified based on the type of energy used, namely thermal and none-thermal desalination (e.g., reverse osmosis, crystallization, and electrodialysis), as shown in Figure 6a [51], and the desalination technologies themselves are classified into two categories: water separation and salt separation (Figure 6b) [51]. Wastewater treatment may be classified into primary, secondary, and tertiary schemes, as shown in Figure 7 [52,53].…”
Section: Desalination and Wastewater Treatment For Marginal Water Reusementioning
confidence: 99%
“…Desalination technologies include several processes that may be classified based on the type of energy used, namely thermal and none-thermal desalination (e.g., reverse osmosis, crystallization, and electrodialysis), as shown in Figure 6a [51], and the desalination technologies themselves are classified into two categories: water separation and salt separation (Figure 6b) [51]. Wastewater treatment may be classified into primary, secondary, and tertiary schemes, as shown in Figure 7 [52,53].…”
Section: Desalination and Wastewater Treatment For Marginal Water Reusementioning
confidence: 99%
“…The European Union proposed a new regulation in May 2020 regarding the reclaimed water minimum quality requirements that should be implemented in the agriculture sector in all member states that are supposed to be implemented from June 2023 [88]. Finally, it was concluded that there are several guidelines set for water reuse worldwide; however, there is no universal standard guideline established for reclaimed water to facilitate large-scale applications [109].…”
Section: Guidelines Set For Water Reusementioning
confidence: 99%